Concept of Cluster Functioning on the Example of Seanergia Cluster – Study Case (Research Bulletins of the Faculty of Economic Sciences, 2018)
The subject of the article is a cluster concept that is an important element of regional innovation systems. Clusters as innovativeness for business are most of all meant as cooperation and development between business entities. Clusters are a relatively new element that plays a fundamental role in developing possibilities of a regional business. The aim of this article is to introduce the cluster functioning, basing on the example of Baltic cluster sEaNERGIA that covers West Pomeranian and Pomeranian voivodeships. In the conducted According to the hypothesis in the conducted research, clusters influence the technological development of businesses and the implemented innovations, as well as sustainable development of the region. Adopted research method is based on the analysis of scientific literature and the overview of materials published online which relate to the topic. Analyses have proven that clusters create positive conditions for development of new and innovative solutions, introducing new products and technologies in the market. A very dynamic development of regional clusters has been observed.
Keywords: cluster, innovativeness, cooperation, business cooperation, cluster designing